INSTITUTIONAL SUPPORT FOR THE SET-UP OF INNOVATION ECONOMY GROWTH POINTS IN RUSSIA - T. Popadyuk; Y. Bogachev; N. Abdikeyev (Управленческие науки, 2016)
Russia possesses intellectual resources, which accumulate the potential of the sixth technological tier technologies.Concentration, organization and reproduction of these intellectual resources, their transformation into breakthrough technologies, building-up of the production system for their development may turn into points of growth in Russia and, with the appropriate institutional support, will promote economic growth based on innovation.The present institutional support of the points of economic growth in Russia does not allow, because of its fragmentariness, to coordinate the interaction of the various stages of the innovation cycle and all structural elements of the national innovation system, and prevents from solving the problem of industrial and commercial development of breakthrough technologies.The article2 substantiates the proposals for institutional support for setting up innovative economy points of growth in Russia based on network principles.